A Correlational Study on Savings, Spending, Investment and Insurance Among Students at Tertiary Levels - Zuraina, Ali (Academic Research Publishing Group, 2018)
The recent economic crisis has heightened the need for the society in Malaysia to manage their financial decision making. Such implies that the knowledge on financial literacy seems to be paramount to be equipped with the Malaysians so as to navigate the complexities of managing one’s life. Taking the statement into account, the current study attempts to examine the correlations of an independent variable; savings behaviour with that of three dependent variables - behaviour in spending, knowledge of investment and knowledge of insurance among students at tertiary levels. A survey research method is employed to obtain its data among 229 volunteered students studying in various academic institutions. The results of the study reveal that there are medium positive correlations between savings and spending as well as investment, while there is a small positive correlation between savings and insurance. Such results that are obtained prove that there is a need to improve financial literacy among the participants especially in their knowledge of insurance.